Peningkatan Keterampilan Berpikir Kritis melalui Model Pembeljaran PBL pada Mata Pelajaran IPS di Sekolah Dasar - Fuadah, Nauroh Zahwa; Nugraha, Arya Setya (Lembaga Yasin AlSys, 2025)
This study aims to improve the critical thinking skills of third-grade elementary students in Social Science (IPS) through the Project-Based Learning (PBL) model. This Classroom Action Research (CAR) was conducted in two cycles involving 32 students, consisting of 18 female students and 14 male students, at an elementary school in Gresik, East Java. Data was collected through written tests, Student Worksheets (LKS), observation sheets, and field notes, using both test and non-test data collection techniques. Data analysis employed both qualitative and quantitative methods. The results of the study show significant improvement in students' critical thinking skills, with an average critical thinking score of 86.09 in the second cycle and a completeness rate of 88%. Improvement was observed in indicators such as identifying problems, gathering information, finding solutions, and using logical reasoning. However, students' ability to use clear language still needs further enhancement. Based on the findings, the PBL model proves to be effective in enhancing critical thinking skills in third-grade students in Social Science and is recommended as a sustainable teaching strategy.